Pengaruh financial literacy, childhood experience, financial behaviour terhadap financial satisfaction pada pengguna shoppepay - Rahmawan, Hafidz Okky; Purwanto, Eko (ARKA INSTITUTE, 2023)
This study aims to analyze the effect of financial literacy, childhood experience and financial behavior on financial satisfaction among Shopeepay users among students of the Faculty of Economics and Business UPN Veterans East Java. This type of research is descriptive quantitative with explanatory research design. The research population is students of the Faculty of Economics and Business UPN Veterans East Java for the 2022/2023 academic year who have the criteria of having made transactions and kept their money in the Shopeepay service. The number of samples in this study were 98 people. The sample was taken using the Solvin technique. The instrument used was a Likert scale questionnaire. The analysis tool uses Partial Least Square (PLS). The results of the study show that Financial Behavior has no role in financial satisfaction for shopeepay users. However, Financial Literacy and Childhood Experience have a role in financial satisfaction for shopeepay users. It can be concluded that financial literacy and childhood experience can increase financial satisfaction in ShopeePay users.